Persepsi Mahasiswa FIP angkatan 2016 terhadap pelayanan perpustakaan FIP UNP - Tomy Octovieri; Irsyad Irsyad; Ermita Ermita; Lusi Susanti (Universitas Negeri Padang, 2021)
AbstractThe purpose of this research is to see how the 2016 FIP perception students the FIP UNP Library. Popullation as many 1348 taken from 137 taken from 10% of the population. Instrument used is the survey in the form of scales likert that has been tested validity and reliability. Technique analysis using formulas the average. The result of this research is perception students FIP the 2016 to the public library FIP UNP be in category good.